2022
DOI: 10.3389/fpubh.2022.865328
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Old-Aged Preferences Regarding Various Types of Physical Activity and Chronic Disease Status: A Cross-Sectional Study in Shanghai, China

Abstract: BackgroundA lack of physical activity (PA) is a threat to public health. However, for the elderly, most PA abilities are limited. By focusing on the types and intensity of PA that the elderly can bear, this study aimed to reveal whether preferences regarding types of PA (including housework, transportation, and recreational activities) and their intensity were associated with health status. The main forms of PA include shopping, cooking, cleaning, walking, cycling, various fitness activities and other activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…We posit that RPA may have a stronger effect than OPA and TPA in adults aged 60 and above due to a potentially passive selection of OPA and TPA by older adults (40). Previous research has suggested that this phenomenon could be influenced by the nature of physical activity and psychological factors (41).…”
Section: Discussionmentioning
confidence: 90%
“…We posit that RPA may have a stronger effect than OPA and TPA in adults aged 60 and above due to a potentially passive selection of OPA and TPA by older adults (40). Previous research has suggested that this phenomenon could be influenced by the nature of physical activity and psychological factors (41).…”
Section: Discussionmentioning
confidence: 90%
“…However, in some studies ( 47 ), such as this one, the relationship between physical activity and blood lipids was not statistically significant. Another study group found that there was no statistically significant difference in the amount of exercise between the patients with abnormal blood indexes and the healthy subjects before the diagnosis of chronic diseases ( 58 ). This may explain to some extent why no relationship was found between physical activity and dyslipidaemia.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, demographic variables included sex, age, height, weight, location of registered household, education level, total monthly family income, type of medical insurance, marital status, the status of living with family and willingness to obtain medical service ( 17 ). Additionally, lifestyle variables included regular consumption of meals (always or often or sometimes or seldom or never) and daily sleeping duration (≤6 h or 7–8 h or ≥9 h), in which always, often, sometimes, seldom and never indicated every day, once every 2 to 3 days, once a week, once every 2 or 3 weeks and never.…”
Section: Methodsmentioning
confidence: 99%